PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA MELALUI PENINGKATAN DISIPLIN KERJA PADA KARYAWAN BAGIAN PRODUKSI PT. GENTONG GOTRI SEMARANG - Muhammad Sulthon Ardyansyah; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2014)
This study aims to determine whether there is influence between leadership, compensation on the performance through enhancing work discipline. Population of this research is the production workers of Gentong Gotri Semarang Co., Ltd. and the researchers took 76 workers as respondents. This type of research is explanatory research with primary data collection through questionnaires from using simple random sampling technique. Analysis techniques using validity, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS version 15. The calculation results of multiple linear regression can be shown by the equation Y = 4,432 + 0,600X1 + 0,105X2 – 0,095Y1. Known that jointly leadership, compensation and work discipline effect on performance. Partially, the influence of leadership on performance of 64,7%, amounting to 29,4% compensation and work discipline of 4,2%. Simultaneously, the influence of the leadership and compensation for occupational performance through increased discipline at 71,9%. To improve the performance of their workers, companies should pay attention to the amount of compensation given mainly allowances and incentives, workers will socialize the importance of adherence to the rules. In solving problems that arise leader must also include the workers, as well as job training and job evaluation periodically.